2019
DOI: 10.1111/bju.14696
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the accuracy of multiparametric MRI for predicting prostate cancer pathology and tumour staging in the real world: an multicentre study

Abstract: Objectives To assess the accuracy of multiparametric magnetic resonance imaging (mpMRI) for the detection of significant prostate cancer in men undergoing radical prostatectomy (RP) in an Australian multicentre setting, and to assess concordance between mpMRI and RP for local tumour staging and index lesion locations. Patients and Methods Men who underwent mpMRI within 12 months of RP between January 2013 and August 2016 at three Australian sites were included (Central Coast, NSW, St Vincents Hospital, Melbour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Due to these findings, we utilized in our study a biopsy protocol that comprehended a combined approach of systematic and fusion targeted biopsy, in order to obtain the highest possible accuracy. Kam et al [31], evaluating the accuracy of mpMRI in detecting PCa and tumor staging, reported, on 235 patients, an overall index lesion location concordance between mpMRI and RP histologic report of 75% with a sensitivity that reached 91% in the detection of clinically significant PCa (GS ≥ 7). In a previous study [32], the same authors reported, on 121 patients, a concordance rate for GS between combined biopsy (fusion plus standard) and final histologic report of 58%.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these findings, we utilized in our study a biopsy protocol that comprehended a combined approach of systematic and fusion targeted biopsy, in order to obtain the highest possible accuracy. Kam et al [31], evaluating the accuracy of mpMRI in detecting PCa and tumor staging, reported, on 235 patients, an overall index lesion location concordance between mpMRI and RP histologic report of 75% with a sensitivity that reached 91% in the detection of clinically significant PCa (GS ≥ 7). In a previous study [32], the same authors reported, on 121 patients, a concordance rate for GS between combined biopsy (fusion plus standard) and final histologic report of 58%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sample size was relatively small. Kam et al [41] observed significant improvement in sensitivity for the prediction of EPE (from 30% to 60%) when applying PIRADS v2 compared with v1 in 235 patients. However, this study lacked information on patient characteristics, MRI findings, event rate, confidence intervals, or further outcomes for the different groups.…”
Section: Standardized Reportingmentioning
confidence: 99%
“…Our present analysis suggested a reduction of 414 biopsies/month (95% CI 120, 708; P =0.007), (or 4968 ± 3528 biopsies annually) correlating to the availability of mpMRIp. The study period encompassed PI‐RADS v1 and v2, although both have been validated to have a high negative predictive value (82% for prostate cancer, and 88% for clinically significant prostate cancer, International Society of Urological Pathology [ISUP] ≥2), with PI‐RADS v2 having equivalent specificity but improved sensitivity, enabling clinicians to use a ‘rule out’ strategy for avoiding invasive prostate biopsies, which may explain this result [8,10,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…trial [PRECISION]) [7]. A standardised reporting tool for mpMRIp, the Prostate Imaging -Reporting and Data System (PI-RADS) version 1 (v1) and the current version 2 (v2) have been validated to increase the positive and negative predictive values of performing a biopsy [6][7][8][9][10]. Multiple studies show good correlation of mpMRIp grading to final histopathology confirmed with radical prostatectomy specimens [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation